Hypoglycemia in low birth weight neonates: frequency, pattern, and likely determinants - Saini, Aanchal; Gaur, Bablu Kumar; Singh, Parvinder (International Journal of Contemporary Pediatrics, 2018)
Background: Hypoglycemia is the commonest metabolic disorder of neonates. If not detected in time, it can lead to considerable morbidity and mortality. Hypoglycemia both symptomatic and asymptomatic can lead to long term neurological sequelae. Therefore, it needs early management to prevent brain damage in a developing neonate. The objective to study the frequency and pattern of hypoglycemia in low birth weight neonates (LBW) and the factors associated with hypoglycemia. Methods: All neonates less than 2500 gm were carefully examined, and a detailed antenatal, natal and postnatal history was obtained. The measurement of blood glucose was estimated by glucometer by taking blood sample by prewarmed heel prick and the same time venous blood sample was sent for laboratory confirmation by glucose oxidase method. Blood glucose was estimated by glucometer at 0, 1, 2, 3, 6 and every 6 hours till 72 hours and the clinical profile of these neonates was recorded. Results: Out of 50 neonates, 12 (24%) had one or more episode of hypoglycemia overall 20 episodes were recorded 15(75%) in first 24 hours and 5(25%) between 49-72 hours all the episodes were asymptomatic. Out of 12 hypoglycemic neonates 7 (58.3%) were small for gestational age (SGA) and 5 (41.7%) were AGA (P = ns). Sepsis was significantly noticed after hypoglycemia (p = 0.00). The pattern of blood glucose levels was significantly different among hypoglycemic babies and normoglycemic babies over first72 hours. Conclusions: Hypoglycemia was frequent among low birth weight babies more so in SGA babies in first 24 hours.